Savings and investment: an evidence from selected Asian countries - Nur Azuanah Masri (2016)
This study proposed to determine the relationship between savings and investment in selected ASEAN countries In perfect capital mobility, saving and investments should not be correlated by each other because if both of these indicators highly correlated, it will show low capital mobility in a country, In addition, this study will investigate the causality between saving and investment in selected ASEAN counties This study would use six of ASEAN countries, namely, Malaysia, Indonesia, Philippines, Thailand, Vietnam and Singapore. This study would use the annual data that covered from 1980 until 2014 that were collected from International Monetary Fund (IMF) and, using the panel cointegration, panel FMOLS, panel DOLS and panel causality to examine the relationship between saving and investment in six of Southeast Asian countries. The result found that existed long-run, short-run and causality relationship between savings and investment in six ASEAN countries over the period 1980 until 2014.